Gene panel sequencing in heritable thoracic aortic disorders and related entities – results of comprehensive testing in a cohort of 264 patients - Campens, Laurence; Callewaert, Bert; Muiño Mosquera, Laura; Renard, Marjolijn; Symoens, Sofie; De Paepe, Anne; Coucke, Paul; De Backer, Julie (Orphanet Journal of Rare Diseases, 2015)
Abstract Background Heritable Thoracic Aortic Disorders (H-TAD) may present clinically as part of a syndromic entity or as an isolated (nonsyndromic) manifestation. About one dozen genes are now available for clinical molecular testing. Targeted single gene testing is hampered by significant clinical overlap between syndromic H-TAD entities and the absence of discriminating features in isolated cases. Therefore panel testing of multiple genes has now emerged as the preferred approach. So far, no data on mutation detection rate with this technique have been reported. Methods We performed Next Generation Sequencing (NGS) based screening of the seven currently most prevalent H-TAD-associated genes ( FBN1 , TGFBR1/2 , TGFB2 , SMAD3 , ACTA2 and COL3A1 ) on 264 samples from unrelated probands referred for H-TAD and related entities. Patients fulfilling the criteria for Marfan syndrome (MFS) were only included if targeted FBN1 sequencing and MLPA analysis were negative. Results A mutation was identified in 34 patients (13%): 12 FBN1 , one TGFBR1 , two TGFBR2 , three TGFB2 , nine SMAD3 , four ACTA2 and three COL3A1 mutations. We found mutations in FBN1 (N = 3), TGFBR2 (N = 1) and COL3A1 (N = 2) in patients without characteristic clinical features of syndromal H-TAD. Six TAD patients harboring a mutation in SMAD3 and one TAD patient with a TGFB2 mutation fulfilled the diagnostic criteria for MFS. Conclusion NGS based H-TAD panel testing efficiently reveals a mutation in 13% of patients. Our observations emphasize the clinical overlap between patients harboring mutations in syndromic and nonsyndromic H-TAD related genes as well as within syndromic H-TAD entities, justifying a widespread application of this technique.